A Single Botulinum Toxin Injection in the Treatment of Strabismus: A Retrospective Analysis of 29 Patients - Shatnawi, Raed; Al-latayfeh, Motasem; Rawashdeh, Moutaz; Shweiki, Samar (Jordan Medical Journal, 2022)
Objective: To describe the change in angle deviation, treatment effectiveness, overall safety, and cost effectiveness of the use of a single botulinum toxin injection session in the treatment of strabismus. Methods: A retrospective analysis at a tertiary hospital in Amman, Jordan, to identify 29 patients who received a single botulinum toxin injection as a treatment of strabismus between October 2017 and March 2019. The outcome was determined by the improvement of the angle of deviation and avoidance of conventional muscle surgery. The safety profile was determined according to the incidence of adverse effects, such as overcorrection and ptosis. The economic profile included the medical and non-medical costs. Results: The average of the total angles of deviation for the whole group improved in the first assessment visit in the first week post injection from 38.97 to 19.48 prism diopter (PD). However, the deviation started to increase after the first month and continued to increase, reaching 27.93 PD in the sixth month post injection follow up. About five of the 29 patients (17.2%) had a successful outcome (angle of deviation equal to or less than 10 PD) in the sixth month post injection, while around seven of the 29 patients (24.1%) had a partial improvement and 17 of the 29 patients (58.7%) had no improvement. Only two patients (6.8%) developed overcorrection. None of the patients developed ptosis or other adverse effects after injection. The total average cost of treatment, including medical and non-medical costs, was $410. The average medical cost was $305, while the non-medical cost was $105. Conclusion: The use of a single botulinum toxin injection for treating strabismus is an effective, safe, and quick procedure to treat strabismus in some patients, especially those with mild and moderate angles of deviation. However, due to the temporary effect of the drug, it needs to be repeated for some patients and thus may be unsatisfactory in some circumstances.